2011
DOI: 10.1021/ef200279v
|View full text |Cite
|
Sign up to set email alerts
|

Energy Requirements for Butanol Recovery Using the Flash Fermentation Technology

Abstract: Acetone–butanol–ethanol (ABE) facilities have traditionally presented unattractive economics because of the large energy consumption during recovery of the products from a dilute fermentation broth (∼13 g/L butanol). This problem results from the high toxicity of butanol to microorganisms that catalyze its production. Flash fermentation is a continuous fermentation system with integrated product recovery. The bioreactor is operated at atmospheric pressure and the broth is circulated in a closed loop to a vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
24

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 24 publications
3
66
0
24
Order By: Relevance
“…As a result, the partial vaporization of the fermentation broth, in a separate vacuum unit, would generate a vapour phase richer in solvents (ABE) and an ABE-depleted liquid stream. [5][6][7] A schematic diagram of the continuous fermentation process with an integrated vacuum unit that was evaluated in this study is presented in Figure 1. In the vacuum-integrated process, a stream is continuously withdrawn from the fermentation broth and passed through a heat exchanger to provide the necessary energy input to sustain the desired evaporation rate before entering a vacuum flash unit, in which a fraction of the inlet stream is then vaporized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the partial vaporization of the fermentation broth, in a separate vacuum unit, would generate a vapour phase richer in solvents (ABE) and an ABE-depleted liquid stream. [5][6][7] A schematic diagram of the continuous fermentation process with an integrated vacuum unit that was evaluated in this study is presented in Figure 1. In the vacuum-integrated process, a stream is continuously withdrawn from the fermentation broth and passed through a heat exchanger to provide the necessary energy input to sustain the desired evaporation rate before entering a vacuum flash unit, in which a fraction of the inlet stream is then vaporized.…”
Section: Methodsmentioning
confidence: 99%
“…All these techniques have advantages and disadvantages in terms of capacity, selectivity, energy requirements, and most importantly the cost. [4][5][6] Studies have shown that conventional ABE fermentation facilities have always had unattractive economics. [5,7] Incorporating an in situ separation technique to partly remove ABE solvents during the course of fermentation increases productivity, but at the expense of additional process complexity and cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por sua vez, a produção de solventes como o etanol e butanol a partir de resíduos tende a aumentar diretamente o balanço energético em biorrefinarias (Xie et al, 2014 (Mariano et al, 2011). A solventogênese constitui um processo subsequente à acidogênese, uma vez que os solventes são obtidos a partir da conversão dos ácidos orgânicos (biohidrogenação), especialmente o butirato e acetato (Harde et al, 2016), sob condições controladas de pH e tamponamento.…”
Section: Biorrefinarias: Conceitos E Potencialidades Da Biodigestão Aunclassified
“…A solventogênese constitui um processo subsequente à acidogênese, uma vez que os solventes são obtidos a partir da conversão dos ácidos orgânicos (biohidrogenação), especialmente o butirato e acetato (Harde et al, 2016), sob condições controladas de pH e tamponamento. 23 O ácido butírico pode ser usado como matéria-prima para produção de butanol, caracterizado como um biocombustível promissor (Mariano et al, 2011), tanto pelo emprego de rotas catalíticas (Sjöblom et al, 2015) quanto por bioquímicas (Regestein et al, 2015). N-butil butirato ou butanoato de butila, um combustível alternativo para aviação, também pode ser obtido a partir do ácido butírico por meio de sua esterificação com o butanol (Sarma et al, 2015;Sjöblom et al, 2015).…”
Section: Biorrefinarias: Conceitos E Potencialidades Da Biodigestão Aunclassified